Comparative Analyses of Financial Stability Ratios. - Tepoyan, Vahagn (Bulletin of Yerevan University G: Economics, 2018)
The most important precondition of economic development is financial stability. In this article, financial stability ratios are represented as well as financial stability definitions. It is also considered to be one of the main problems of the Central Bank of the Republic of Armenia. In the financial system of RA, banks play a dominant role. In substance, the stability of banks is a characteristic of financial system stability. A comparative analysis of the financial stability ratios of Armenia and Eurasian Economic Union is also made.